STUDI TENTANG IKLIM SEKOLAH DI KABUPATEN LUWU - Sugiarto Sugiarto (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
This researched focused in school climate at SMA Negeri 4 Luwu include school environment, school regulation, principal’s leadership, and interpersonal relation. Data source of this research were principle, teachers, staffs, and students of SMA Negeri 4 Luwu in Luwu Regency. Data collecting by using interview, observation and documentation. Data was analized by data reduction, data display and conclusion/verification. The research shows that there are four aspects of the school climate related to the conditions of the school climate, namely aspects of the school environment which include the cleanliness of the school environment and the regularity of the school environment, school rules which include school rules and penalties or sanctions, principal leadership which includes motivation and cooperation, and relationships. interpersonal relationships that create mutual respect, mutual trust, and caring relationships between school members.